Spontaneous fractures and hypocuprosis in pen-backgrounded Holstein calves - Castro, Damian Jesus Nahuel; Mattioli, Guillermo Alberto; Margineda, Carlos Augusto (Brazilian Association of Veterinary Pathology, 2023)
Bone fractures are a frequent cause of limp in cattle, being pre-existing bone lesions among the predisposing factors. However, there is scant information about the natural occurrence of bone disease. This report aimed to describe an outbreak of spontaneous fractures associated with hypocuprosis in pen-backgrounded calves. Hind limp and irreversible recumbency were noticed in 9-month-old calves of a dairy farm from Córdoba province (Argentina). The issue was only evident in males fed a diet composed (DM) of 57% wet corn, 24% dry corn distiller grains, and 19% corn silage. No mineral mix was supplied. Accumulated morbidity and fatality rates were 5.8 and 100%, respectively. Two autopsies were performed, observing multiple femoral and rib fractures. Severe hypocupremia, very low copper levels in the liver and plasma, deficient dietary copper levels, normocalcemia, marginal hypophosphatemia, and high sulfate concentrations in the water supply were determined. Except for the decreased bone quantity and the multiple fractures, no bone lesion was observed, confirming osteoporosis as the pathological diagnosis, and hypocuprosis as the etiology.